Olympic Games during nationwide lockdown: sports injuries and illnesses, including COVID-19, at the Beijing 2022 Winter Olympics - Soligard, T.; Palmer, D.; Steffen, K.; Lopes, A. D.; Grek, N.; He, X.; Wang, Y.; Grant, M.-E.; Toresdahl, B. G.; Gilgien, M.; Budgett, R.; Engebretsen, L. (British Journal of Sports Medicine, 2024)
Objective The objective of this study is to describe the incidence of injuries and illnesses sustained during the Beijing Winter Olympic Games from 4 February 2022 to 20 February 2022.